Probing A-form DNA: A fluorescent aminosugar probe and dual recognition by anthraquinone-neomycin conjugates. Issue 4 (15th February 2017) - Watkins, Derrick; Gong, Changjun; Kellish, Patrick; Arya, Dev P.
Graphical abstract: Abstract: Nucleic acids adopt a broad array of hydrogen-bonded structures that enable their diverse roles in the cell; even the familiar DNA double helix displays subtle architectural nuances that are sequence dependent. While there have been many approaches for recognition of B-form nucleic acids, A-form DNA recognition has lagged behind. Here, using a tight binding fluorescein-neomycin (F-neo) conjugate that can probe the electrostatic environment of A-form DNA major groove, we developed a fluorescent displacement assay to be used as a screen for DNA duplex-binding compounds. As opposed to intercalating dyes that can significantly perturb DNA structure, the groove binding F-neo allows the probing of native DNA conformation. In combination with the assay development and probing of DNA grooves, we also report the synthesis and binding of a series of neomycin-anthraquinone conjugates, two units with a known preference for binding GC rich DNA. The assay can be used to identify duplex DNA-binding compounds, as well as probe structural features of a target DNA duplex, and can easily be scaled up for high throughput screening of compound libraries.